2018
DOI: 10.14719/pst.2018.5.3.398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fast and slow desiccation on Garcinia imberti seed and seedling vigour

Abstract: Garcinia imberti Bourd. endemic to the southern Western Ghats is classified as endangered by the IUCN (2018). The seeds as the sole means of propagation with initial moisture content (MC) of 62.8% are sensitive to desiccation. Studies on the responses of the seed to drying require ascertaining of the critical moisture content (CMC) as a basic requisite for germplasm conservation. Responses of G. imberti seeds to fast drying with activated silica gel (25 ± 2 °C, 6 ± 1% RH) and to slow drying under laboratory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Baskin and Baskin (18) reported that seed dormancy is usually allied with intrinsic factors linked to the seed itself, such as rigid and impermeability of the seed coat to gases and water, immature embryos, inhibitors, and abiotic factors like temperature, humidity, light and substrate. The G. imberti seeds when subjected to decoating, dormancy were also reduced (8). The seed decoating was efficient for avoiding the inhibitory phyto-compounds present (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baskin and Baskin (18) reported that seed dormancy is usually allied with intrinsic factors linked to the seed itself, such as rigid and impermeability of the seed coat to gases and water, immature embryos, inhibitors, and abiotic factors like temperature, humidity, light and substrate. The G. imberti seeds when subjected to decoating, dormancy were also reduced (8). The seed decoating was efficient for avoiding the inhibitory phyto-compounds present (19).…”
Section: Discussionmentioning
confidence: 99%
“…Garcinia imberti is an evergreen, endangered tree species (7) growing up to 10 m height bearing recalcitrant seeds with high moisture content. The niche specificity is due to its patchy, specific altitudinal (600-1200 m asl) distribution, recruitment failure due to high fruit/seed predation and a prolonged period of seed dormancy (8). The major difficulty in G. imberti propagation as for many species of Garcinia genus is related to its seeds germination, dormancy and storage aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation